2022
DOI: 10.1108/jmtm-06-2022-0235
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of fusion-based additive manufacturing technologies on green supply chain management performance

Abstract: PurposeThis paper aims to identify the impacts of wire and arc additive manufacturing (WAAM) technology on the green supply chain management (GSCM) performance. Also, it intends to identify the most essential WAAM capabilities.Design/methodology/approachAn exploratory case study related to a metallurgical company using WAAM technology to repair metallic components was developed. A research framework to identify WAAM production capabilities and the different GSCM performance criteria was proposed based on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…From the analysis of the literature, several articles were found that studied sustainable performance indicators. Ferreira et al (2023) examined the impact of fusion based additive manufacturing technologies on GSCM performance. Sheng et al (2023) reviewed the GSCM in integration with China's manufacturing industry.…”
Section: Gscm Performance Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…From the analysis of the literature, several articles were found that studied sustainable performance indicators. Ferreira et al (2023) examined the impact of fusion based additive manufacturing technologies on GSCM performance. Sheng et al (2023) reviewed the GSCM in integration with China's manufacturing industry.…”
Section: Gscm Performance Measuresmentioning
confidence: 99%
“…In previous studies, much attention has been given to the traditional supply chain model of production and consumption rather than the green and lean aspects of the supply chain. The green supply chain is different from the traditional one as it acknowledges the ecological impact in decision making (Ferreira et al, 2023;Rupa and Saif, 2022). The green trend of protecting the environment and conserving the Earth's resources is a prime focus due to increased awareness about environmental protection (Pal et al, 2023;Panpatil and Kant, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streamline production activities, reduce lead times, and improve overall productivity (Anzolin & Andreoni, 2023;Bueno et al, 2020;Krzywdzinski & Jo, 2022;Mortimer, 2006;Syed et al, 2020;Wilson, 2010) 3D printing Enables on-demand production, reducing lead times, inventory costs, and waste (Bueno et al, 2020;Chi et al, 2022;Dilberoglu et al, 2017;Ferreira et al, 2023;Savsani et al, 2023) systematic planning, implementation, and monitoring of all activities to improve product quality or services, thereby enhancing customer satisfaction (Claver et al, 2003). I4.0 technologies can enhance customer satisfaction when integrated with QM principles such as Total Quality Management (TQM), Six Sigma, Lean Manufacturing, and ISO Standards (Chiarini, 2020;Nicholas, 2016;Patyal & Maddulety, 2015).…”
Section: Robots and Automationmentioning
confidence: 99%
“…Specifically, as suppliers have closed or downsized, the original molds no longer exist, making it challenging to fabricate replacement parts [1]. Wire arc directed energy deposition (Wire Arc DED), an additive manufacturing (AM) technique using an electric arc to melt and deposit metal layer-by-layer, has presented itself as a potential solution to this problem [3]. With the capability to manufacture parts with less material waste, increased design flexibility, rapid prototyping [4], and its higher deposition rate, material utilization, and energy efficiency [5,6], research dedicated to Wire Arc DED manufacturing has grown in recent years [7].…”
Section: Introductionmentioning
confidence: 99%